Generation of the therapeutic monoclonal antibody NEO-201, derived from a cancer vaccine, which targets human malignancies and immune suppressor cells - Massimo Fantini; Kwong Y. Tsang; Philip M. Arlen (Taylor & Francis Group, 2024)
Introduction Cancer vaccines stimulate the activation of specific humoral and cellular adaptive responses against cancer cells.Antibodies generated post vaccination can be isolated and further selected to develop highly specific and potent monoclonal antibodies (mAbs) against tumor-associated antigens.Areas covered This review describes different types of cancer vaccines, the process of the generation of the mAb NEO-201 from the Hollinshead cancer vaccine platform, the characterization of the antigen recognized by NEO-201, the ability of NEO-201 to bind and mediate the killing of cancer cells and immunosuppressive cells (gMDSCs and Tregs) through ADCC and CDC, NEO-201 preclinical and clinical toxicity and efficacy.Expert opinion To overcome the problem of poor clinical efficacy of cancer vaccines, due to the activity of immunosuppressive cells, cancer vaccines could be combined with other immunotherapeutics able to deplete immunosuppressive cells. Results from clinical trials, employing NEO-201 alone or in combination with pembrolizumab, showed that durable stabilization of disease after treatment was due to the ability of NEO-201 to target and reduce the percentage of circulating Tregs and gMDSCs.These findings provide compelling support to combine NEO-201 with cancer vaccines to reintegrate their ability to elicit a robust and durable immune adaptive response against cancer.